Does Financial Inclusion Affect Health Among Older Adults? Evidence from Indonesia - Abdurrahman, Adnan; Haryanto, Tri (Signifikan: Jurnal Ilmu Ekonomi, 2023)
While financial inclusion is widely acknowledged as a means to enhance the welfare of all ages, currently, there is no empirical research examining its effects on the health of older adults in Indonesia. This study, therefore, aims to fill the gap by investigating the impact of financial inclusion on the health of older adults in Indonesia using data from the March 2021 National SocioEconomic Survey (SUSENAS). The binary logistics regression was used to assess that effect. The findings reveal that financial inclusion positively benefits the health of older adults in Indonesia, highlighting the importance of policy-making that promotes financial inclusion programs to improve the health outcomes of older adults.JEL Classification: G2, I1, C31How to Cite:Abdurrahman, A., & Haryanto, T. (2023). Does Financial Inclusion Affect Health among Older Adults? Evidence from Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 327-340. https://doi.org/10.15408/sjie.v12i2.32001